HASMONAEAN MODIʽIN AND BYZANTINE MODITHA: A TOPOGRAPHICAL–HISTORICAL AND ARCHAEOLOGICAL ASSESSMENT. (December 2015) - Zissu, Boaz; Perry, Lior
Abstract : The location of ancient Modi'in, the hometown of the Hasmonaeans – as mentioned in 1 Maccabees and the writings of Josephus – has been in dispute ever since geographical–historical research on the site began. In this paper we explore the various possible locations for Modi'in and propose a different geographical solution to the problem.